Keefektifan Model Blended Learning Terhadap Kemampuan Memahami Bacaan Tema 1 Organ Gerak Hewan dan Manusia Subtema 1 Organ Gerak Hewan Kelas V SD N Sendangasri Rembang - Achmad Taufan Wahyuningdikdo; Ikha Listyarini; Filia Prima Artharina (STKIP Andi Matappa Pangkep, 2022)
One-group pretest-posttest design was employed in the study.The study's participants were all fifth-graders at SDN Sendangasri Rembang. Saturated Sampling was used to collect samples from 22 fifth-grade children. Research instruments, pretests, posttests, documentation, and observation sheets were used to collect data for the study.It was determined that tcount = 5.622 based on the findings of the data analysis. The result is 2.080 when compared to the value of ttable at db = 21 with a level of = 0.05. If tcount equals ttable, the hypothesis is accepted. As a consequence of the calculations, tcount > ttable was achieved, andHo was accepted. This indicates that the average pretest and posttest scores differ. According to the calculations, the posttest has 20 students (91%) who have attained the KKM with an average posttest score of 72.2, but the pretest has just 6 students (27%) who have reached the KKM with an average learning outcome. pretest = 57.9%; posttest = 57.9%; posttest = 57 The completion rate of traditional learning in the posttest was 75%, indicating that blended learning is beneficial in improving the learning outcomes of class V students. Animal and Human Movement Organs (Theme 1) Animal Movement Organs is the first sub-theme.